New media impacts on senior citizen's behaviours - Mohammad Razi, Siti Aishah; Syed Zainudin, Sharifah Sofiah; Lim, Michelle (Faculty of Medicine and Health Science, 2022)
Technology has the ability to enhance the lives of senior citizens, especially for communication and interpersonal relationships purposes. This study evaluates the impact of new media usage on senior citizen’s behaviours, particularly in Serdang, Selangor. The survey questionnaire was distributed to 145 participants, which based on purposive sampling. The findings indicate that new media usage has a positive impact on the behaviours of senior citizen. Many of senior citizens utilised new media to satisfy certain goals and needs, such as to gain knowledge, experience a pleasure, seek to interact online, shift attention and to improve their self-confidence.